Analisis Penggunaan Kata Tabu Dialog Jawa Timuran dalam Cuplikan Youtube “Yowis Ben 2” (Kajian Sosiopragmatik) - Kasmanah; Muhammad Kamal bin Abdul Hakim; Miftahulkhairah Anwar (Jurnal Ilmu Pendidikan dan Sosial, 2022)
The language used as a medium of communication for someone to convey ideas or thoughts must pay attention to the norms, situations, and conditions of the language being spoken. Because inaccuracy in using language often triggers conflict in certain communities. This can be influenced by the development of language and culture such as the emergence of taboo words that are not appropriate in using and interpreting them. In the upload of the YouTube channel "Yowis Ben 2" describes a dialogue between two characters discussing taboo words in their daily speech and there is a new meaning expressed by the character. The purpose of this study is to analyze the use of taboo words in East Javanese dialogue in the YouTube clip "Yowis Ben 2". This study uses a qualitative sociopragmatic approach with text analysis methods and the content of YouTube broadcasts. The data collection technique used is the technique of listening, speaking, and taking notes, then narrated and documented. Based on the results of the study, the use of taboo words in East Javanese dialogue on the YouTube channel "Yowis Ben 2" starring Bayu Skak and Anya Geraldine. The words 'jancuk' and 'barokokok' were found. The word, which was originally a taboo word, has now changed its meaning to be positive, namely expressing the expression of the heart, cultural expression in behavior, and containing hyperbolic meaning. The expression is used only in certain circles who understand the function of the words 'jancuk' and 'barokokok'. In its use, it must be accompanied by a supportive expression, namely a smiling, happy, and amazed face and the tone of voice should not be high when the word 'jancuk' is said. This is what distinguishes the expression of the word 'jancuk' from the meaning of the taboo word that has been understood so far and it can be concluded that the word 'jancuk' becomes a positive word when its use is in accordance with the criteria that have been explained.